Revisiting essential hypertension, regulation of blood pressure control and the Adrenaline Hypothesis - Abdullah, Aszrin; Mohd Shah, Azarisman Shah; Mohd Noor, Noriah; Abdul Razak, Tariq (IIUM, 2015)
Hypertension or high blood pressure (BP) is a condition that has a significant impact on the world's population morbidity and mortality. The World Health Report 2002, stated that high blood pressure caused 7.1 million deaths throughout the world, which was approximately 13% of total deaths worldwide. The body's arterial blood pressure control depends on short-term and long-term mechanisms. Short-term BP regulation is mediated by the autonomic nervous system (ANS) targeting the heart, vessels, and adrenal medulla. The sympathetic nervous systems (SNS) crucial involvement in stressful conditions and short term regulation of blood pressure is also widely accepted. There has also been increasing evidence and recognition of sympathetic augmentation as the main cause for essential hypertension in a significant number of patients especially those with no known attributable secondary causes and those who are young. We discuss the role of the adrenaline hypothesis in the pathophysiology of hypertension.